Efficacy of morin on serum and heart tissue lipids in rats subjected to isoproterenol-induced myocardial injury - Al-Numair, Khalid S.; Govindasamy, Chandramohan; Alsaif, Mohammed A.; Veeramani, Chinnadurai (Progress in Nutrition, 2014)
Lipids and lipoproteins play an important role in the pathology of myocardial infarction. In our early study shows, pretreatment with morin, a flavonoid, ameliorates cardiac markers, adenosine triphosphatases and glycoprotein’s in isoproterenol (ISO) induced myocardial infarction in rats at the optimum dose of 40 mg/kg BW. The present study evaluated the flavonoid-morin on lipid profiles in isoproterenol (ISO) induced myocardial infarction in rats. Male albino Wistar rats were pretreated with morin at the optimum dose of 40 mg/kg daily for a period of 30 days. After the treatment period, ISO (85 mg/kg) was subcutaneously injected in rats at an interval of 24 h for 2 days. ISO caused a significant increase in the activity of total cholesterol (TC), cholesterol ester (CE), free cholesterol (FC), triglycerides (TG), free fatty acids (FFA) and phospholipids (PL), low density lipoprotein-cholesterol (LDL-C) and very low density lipoprotein-cholesterol (VLDL-C) in serum and decreased activities in heart phospholipids, serum high density lipoprotein-cholesterol (HDL-C) levels. Pre-treatment with morin at 40 mg/kg dose blocked these changes to normality which proved their antihyperlipidemic action. These findings provided evidence that morin was found to be protecting the myocardium against ischemic insult and the protective effect could attribute to its antihyperlipidemic activities.